A combination of low serum concentrations of vitamins K1 and D is associated with increased risk of hip fractures in elderly Norwegians: a NOREPOS study. Issue 4 (April 2016) - Finnes, T.; Lofthus, C.; Meyer, H.; Søgaard, A.; Tell, G.; Apalset, E.; Gjesdal, C.; Grimnes, G.; Schei, B.; Blomhoff, R.; Samuelsen, S.; Holvik, K.
Abstract Summary The present study investigated the risk of incident hip fractures according to serum concentrations of vitamin K1 and 25-hydroxyvitamin D in elderly Norwegians during long-term follow-up. The results showed that the combination of low concentrations of both vitamin D and K1 provides a significant risk factor for hip fractures. Introduction This case-cohort study aims to investigate the associations between serum vitamin K1 and hip fracture and the possible effect of 25-hydroxyvitamin D (25(OH)D) on this association. Methods The source cohort was 21, 774 men and women aged 65 to 79 years who attended Norwegian community-based health studies during 1994–2001. Hip fractures were identified through hospital registers during median follow-up of 8.2 years. Vitamins were determined in serum obtained at baseline in all hip fracture cases (n  = 1090) and in a randomly selected subcohort (n  = 1318). Cox proportional hazards regression with quartiles of serum vitamin K1 as explanatory variable was performed. Analyses were further performed with the following four groups as explanatory variable: I: vitamin K1  ≥ 0.76 and 25(OH)D ≥ 50 nmol/l, II: vitamin K1  ≥ 0.76 and 25(OH)D < 50 nmol/l, III: vitamin K1  < 0.76 and 25(OH)D ≥ 50 nmol/l, and IV: vitamin K1  < 0.76 and 25(OH)D < 50 nmol/l. Results Age- and sex-adjusted analyses revealed an inverse association between quartiles of vitamin K1 and the risk of hip fracture. Further, a 50 % higher risk of hip fracture was observed in subjects with both low vitamin K1 and 25(OH)D compared with subjects with high vitamin K1 and 25(OH)D (HR 1.50, 95 % CI 1.18–1.90). The association remained statistically significant after adjusting for body mass index, smoking, triglycerides, and serum α-tocopherol. No increased risk was observed in the groups low in one vitamin only. Conclusion Combination of low concentrations of vitamin K1 and 25(OH)D is associated with increased risk of hip fractures.